Homeopathic remedies as metaphors in family therapy. A narrative-based approach to homeopathy - Konitzer, M; Renée, A; Doering, T (Homeopathy, 2003)
Objective: To examine a metaphorical, narrative model to explain the outcome of an homeopathic encounter involving the patient, practitioner and the homeopathic medicine.Material and Methods: The transcript of a videotaped doctor–patient interaction from a European doctor–patient communication study (EUROCOM) was analysed using qualitative methods.Results: Analysis demonstrates a narrative relationship between the protagonists in the therapeutic interaction, with the homeopathic medicine performing a metaphorical role.Discussion: The results justify further investigation of the narrative and metaphorical properties of the therapeutic encounter in homeopathy.
Keywords: homeopathy; metaphor; narrative-based medicine; qualitative research